Intravitreal gene therapy protects against retinal dysfunction and degeneration in sheep with CLN5 Batten disease. (June 2021) - Murray, Samantha J.; Russell, Katharina N.; Melzer, Tracy R.; Gray, Steven J.; Heap, Stephen J.; Palmer, David N.; Mitchell, Nadia L.
Abstract: Neuronal ceroid lipofuscinoses (NCL; Batten disease) are a group of inherited neurodegenerative diseases primarily affecting children. A common feature across most NCLs is the progressive loss of vision. We performed intravitreal injections of self-complementary AAV9 vectors packaged with either ovine CLN5 or CLN6 into one eye of 3-month-old CLN5 −/− or CLN6 −/− animals, respectively. Electroretinography (ERG) was performed every month following treatment, and retinal histology was assessed post-mortem in the treated compared to untreated eye. In CLN5 −/− animals, ERG amplitudes were normalised in the treated eye whilst the untreated eye declined in a similar manner to CLN5 affected controls. In CLN6 −/− animals, ERG amplitudes in both eyes declined over time although the treated eye showed a slower decline. Post-mortem examination revealed significant attenuation of retinal atrophy and lysosomal storage body accumulation in the treated eye compared with the untreated eye in CLN5 −/− animals. This proof-of-concept study provides the first observation of efficacious intravitreal gene therapy in a large animal model of NCL. In particular, the single administration of AAV9-mediated intravitreal gene therapy can successfully ameliorate retinal deficits in CLN5 −/− sheep. Combining ocular gene therapy with brain-directed therapy presents a promising treatment strategy to be used in future sheep trials aiming to halt neurological and retinal disease in CLN5 Batten disease. Highlights: Intravitreal delivery of AAV9 is well tolerated in sheep. Intravitreal AAV9.CLN5 protects against retinal dysfunction in CLN5 −/− sheep. Intravitreal AAV9.CLN5 attenuates retinal pathology in CLN5 −/− sheep.